Advanced Nanocomposite Coatings of Fusion Bonded Epoxy Reinforced with Amino-Functionalized Nanoparticles for Applications in Underwater Oil Pipelines. (27th October 2016) - Saliba, Patricia A.; Mansur, Alexandra A. P.; Mansur, Herman S.
Abstract : The performance of fusion-bonded epoxy coatings can be improved through advanced composite coatings reinforced with nanomaterials. Hence, in this study a novel organic-inorganic nanocomposite finish was designed, synthesized, and characterized, achieved by addingγ -aminopropyltriethoxysilane modified silica nanoparticles produced via sol-gel process in epoxy-based powder. After the curing process of the coating reinforced with nanoparticles, the formation of a homogenous novel nanocomposite with the development of interfacial reactions between organic-inorganic and inorganic-inorganic components was observed. These hybrid nanostructures produced better integration between nanoparticles and epoxy matrix and improved mechanical properties that are expected to enhance the overall performance of the system against underwater corrosion.